(3GdLGeY GdcGaj aj abg GdRjOjIs - (3CHh YHO Gddg eMeO Hf Ydj Hf GdMSf YHO GdQMef Gdchaj GdMSfjs ((3CMeO Hf Ydi Hf YHO Gddg s)
(3ChdgG (B:s
(3Chdg HYO GdHSedI , eSCdI , EPG JRhLgG Ydi YQV agdc GdYQV Ef ESJMb bGd eMeO hEPG JRhL QLd CeQCI Ydi YQV s
(3BNQgG (B:s
(3BNQg ef eSCdI , ZPG CaSOJ GdOGHI RQY bhe djdkG Ch eJGMge fgGQkG bhdg (B: (3hQhi Yf TQjM fMh Pdc , hdjS ddPi CaSOJ Ydjg Cf jMdHgG Je GdLRA GdQGHY , jJdhg ai GdNGeS s
(3GdLRA (B3s
4 (3ef fSNI CNQis
(3cJHJ GdYfhGfGJ HNW eLhOs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis